2022
DOI: 10.1186/s12931-022-02268-3
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity and physical activity in COPD patients treated with a LAMA/LABA combination: a systematic review and meta-analysis

Abstract: Background Persistent airflow limitation and dyspnoea may reduce chronic obstructive pulmonary disease (COPD) patients exercise capacity and physical activity, undermining their physical status and quality of life. Long-acting muscarinic antagonists and long-acting beta-2 agonists (LAMA/LABA) combinations are amongst moderate-to-severe COPD recommended treatments. This article analyses LAMA/LABA combinations effect on COPD patients exercise capacity and physical activity outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…2 Studies examining the efficacy of LABD in patients with COPD reported improvements in forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), inspiratory capacity (IC) and exercise endurance time with dual bronchodilation providing greater efficacy than placebo or monotherapy. [3][4][5][6][7] This was also confirmed in the TORRACTO study, a double-blind, placebo-controlled trial, which demonstrated that tiotropium/olodaterol 5/5 μg (T/O) improved endurance time during constant work-rate cycle ergometry (CWRCE) with 23% and 14% after, respectively, 6 and 12 weeks compared to placebo. 6 In addition, the secondary endpoints, IC at rest (ICrest) and at isotime (ICiso), showed significant expansion confirming the strong association between reduction in hyperinflation and improvement in exercise tolerance.…”
Section: Introductionmentioning
confidence: 68%
“…2 Studies examining the efficacy of LABD in patients with COPD reported improvements in forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), inspiratory capacity (IC) and exercise endurance time with dual bronchodilation providing greater efficacy than placebo or monotherapy. [3][4][5][6][7] This was also confirmed in the TORRACTO study, a double-blind, placebo-controlled trial, which demonstrated that tiotropium/olodaterol 5/5 μg (T/O) improved endurance time during constant work-rate cycle ergometry (CWRCE) with 23% and 14% after, respectively, 6 and 12 weeks compared to placebo. 6 In addition, the secondary endpoints, IC at rest (ICrest) and at isotime (ICiso), showed significant expansion confirming the strong association between reduction in hyperinflation and improvement in exercise tolerance.…”
Section: Introductionmentioning
confidence: 68%
“…In the literature, it is shown that monotherapy of LABDs or SABDs improves exercise tolerance 31 and LAMA/LABA combination therapy improves exercise tolerance and physical activity compared to monotherapy. 32 In two RCTs, when SABA was added to LAMA treatment, home-based exercise training or daily activities showed significant improvement in the 6MWD 33,34 and the additive effect of single inhalation of SABA not SAMA on LAMA on exercise capacity. 35 Additionally, we could not perform a meta-analysis on physical activity after combining SAMA with LABA treatment due to a lack of data.…”
Section: Discussionmentioning
confidence: 97%
“…A number of studies of dual bronchodilators followed, comparing these with placebo or mono-LABD; dual bronchodilation provided improvements in exercise capacity versus placebo, however, the results versus mono-LABD were contradictory. A recent systematic review showed that LABA/LAMA combinations were overall superior to monotherapy in improving exercise capacity; in detail, however, the analysis showed only trends of improvement versus monotherapy in endurance shuttle walk test and constant work rate cycle ergometry, but significantly improved the six-minute walking test and number of steps per day 34 . Interestingly, in some of these studies, with the well-designed MORACTO studies being an example, dual bronchodilation improved lung hyperinflation (both static and importantly dynamic), but not exercise endurance 16 .…”
Section: Improvements In Exercise Capacitymentioning
confidence: 93%